EKSPLOITASI ISTRI SEBAGAI PEKERJA SEKS KOMERSIAL DALAM BENTUK KEKERASAN RUMAH TANGGA (STUDY KASUS SUAMI X PEKANBARU) - Okma Mulia, Rendi; Askarial (UIR PRESS, 2022)
Sexual exploitation are those who are involved in prostitution, services or sex workers or become objects of pornographic activities caused by the economy and exploitation by prostitution of others is an activity to earn money and other benefits from prostitution activities. the theory that researchers use where researchers use rational choice theory why researchers use rational choice theory because rational choice theory intends criminals to think rationally to commit the crimes they commit by knowing the consequences of their actions but also continuing to commit the crimes they commit. Like the case that the researcher studied, this theory is certainly closely related because the husband with his rational choice makes the victim a commercial sex worker to get money and other benefits.